The Muslim Elite School and Their Contribution to Dynamics of Urban Muslim Communities in Indonesia - Nelly Mujahidah; Baidhillah Riyadhi; Choirul Mahfud (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This article's results study aims to know the phenomenon that occurs from development school of elite Muslims in Pontianak City, Indonesia. The elite Muslims School, such as SD Muhammadiyah, SD Islam Al-Azhar 21, and SDIT Al- Mumtaz in Pontianak, is the institution of education that has contributed to making a generation of Muslim scholars in Indonesia. The study was conducted with an approach and qualitative analysis with method data collection via observation, interview, and documentation. Study results in this show: first, awareness of elite Muslims in essential institutions of education-based Islamic values becomes an important moment in schools. Second, curriculum, additional pattern learning, and programs have been based on draft integrative learning. Collaborate curriculum government and curricula formulated in a manner quality independent with permanent based on Islamic values. Third, management based on sources of power is superior and supported by infrastructure and adequate education, so the learning process is also quality. Fourth, participant input educates the Public Muslim class medium top, with established economic, social, and educational levels.